Novel nanosecond semiconductor opening switch for megavolt repetitive pulsed power technology: experiment and applications; Proceedings of the International Symposium on Novel Applications of Lasers and Pulsed Power (Photonics West '95), San Jose, CA, february 6-10, 1995; Vol. 2374 - Kotov Yu. A.; Mesyats G. A. Gennady Andreyevich; Rukin S. N.; Filatov A. L.; Lyubutin S. K. (1995, 1995)
В фонде НТБ ТПУ отсутствует